Optimizing the Role of Correctional Institution in Resolving Cases Through Diversion at the Class I Correctional Institution of Tangerang - Khusnus Sa'bani; Eva Achjani Zulfa (LEGAL BRIEF, 2023)
The implementation of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System depends heavily on the effective functioning of Correctional Institutions (BAPAS) in carrying out their duties as correctional technical implementing units. In the judicial process, BAPAS plays a crucial role in conducting research, providing guidance, supervision, and assistance to criminal children. However, the failure of BAPAS to fulfill its responsibilities could result in the failure to achieve the objectives of the law. This study aims to address the role of BAPAS in optimizing diversion efforts for the settlement of cases involving children facing the law, with a focus on the Class I Correctional Institution of Tangerang from 2019-2021. Specifically, the study investigates the extent to which BAPAS is successful in implementing diversion as a means of addressing cases involving juvenile offenders, and identifies the challenges that BAPAS faces in effectively carrying out its diversion duties. This study utilizes socio-legal research, specifically descriptive analytical research, to thoroughly describe and categorize the object of the subject matter. Primary and secondary legal materials, as well as qualitative analysis, are used to gather and analyze data. The study draws inductive conclusions from the data obtained to provide clarity in problem-solving. The findings of the study reveal that the role of BAPAS is significant in the success of diversion efforts to solve cases involving juvenile offenders. However, the study also identifies several challenges that hinder the effective implementation of diversion in the Class I Correctional Institution of Tangerang, as evidenced by the low number of cases that were effectively addressed through diversion compared to the total number of cases handled